Rapid Sex Chromosome Turnover in African Clawed Frogs (Xenopus) and the Origins of New Sex Chromosomes - Evans, Ben J; Gvoždík, Václav; Knytl, Martin; Cauret, Caroline M S; Herrel, Anthony; Greenbaum, Eli; Patel, Jay; Premachandra, Tharindu; Papenfuss, Theodore J; Parente, James; Horb, Marko E; Measey, John (Molecular biology and evolution, 2024)
Sex chromosomes of some closely related species are not homologous, and sex chromosome turnover is often attributed to mechanisms that involve linkage to or recombination arrest around sex-determining loci. We examined sex chromosome turnover and recombination landscapes in African clawed frogs (genus Xenopus) with reduced representation genome sequences from 929 individuals from 19 species. We recovered extensive variation in sex chromosomes, including at least eight nonhomologous sex-associated regions-five newly reported here, with most maintaining female heterogamety, but two independent origins of Y chromosomes. Seven of these regions are found in allopolyploid species in the subgenus Xenopus, and all of these reside in one of their two subgenomes, which highlights functional asymmetry between subgenomes. In three species with chromosome-scale genome assemblies (Xenopus borealis, Xenopus laevis, and Xenopus tropicalis), sex-specific recombination landscapes have similar patterns of sex differences in rates and locations of recombination. Across these Xenopus species, sex-associated regions are significantly nearer chromosome ends than expected by chance, even though this is where the ancestral recombination rate is highest in both sexes before the regions became sex associated. As well, expansions of sex-associated recombination arrest occurred multiple times. New information on sex linkage along with among-species variation in female specificity of the sex-determining gene dm-w argues against a "jumping gene" model, where dm-w moves around the genome. The diversity of sex chromosomes in Xenopus raises questions about the roles of natural and sexual selection, polyploidy, the recombination landscape, and neutral processes in driving sex chromosome turnover in animal groups with mostly heterogametic females.
Keywords: Sex Determination Processes; sex chromosome turnover; rekombinace genetická; sex determination; genetic linkage; Xenopus; Sex Chromosomes; Male; procesy určující pohlaví; pohlavní chromozomy; Animals; Female; mužské pohlaví; ženské pohlaví; allopolyploidization; zvířata; recombination landscape; Recombination, Genetic